Aprendemos las formas de energía usando material didáctico, maqueta - Mauricio Pascual, Elbis Alberto (2019)
In the present work of learning session called: We learn the forms of energy using didactic material "model" is intended to guide the student to learn more fun to manipulate teaching resources in their learning._x000D_ In the world there are different ways to obtain energy and the human being has looked for ways to use them for their well-being and survival throughout history, so in this learning session the student is encouraged to learn and investigate in a didactic way and innovative in its incentive to discover the world and technology in its environment